Optimalisasi Strategi Retensi Talenta dengan Knowledge Management dan Manajemen Bakat: Studi Kasus di Pemerintah Daerah Provinsi Jawa Barat - Ika Ari Wijayanti; Galih Darmawan Hidayatullah; Rifki Nugraha Nurilahi (Global Leadership Organizational Research in Management, 2025)
This study aims to analyze the role of Knowledge Management (KM) and talent management in talent retention strategies in the West Java Provincial Government. In facing the challenges of competition to retain talented employees in the public sector, these two concepts are expected to increase employee engagement and job satisfaction, which in turn will reduce the turnover rate. This study uses a qualitative approach with a case study method, involving 150 respondents from various West Java Provincial Government agencies, consisting of employees with different backgrounds and positions. Data were collected through in-depth interviews, participant observation, and document analysis. The results of the study indicate that the implementation of KM in the West Java Provincial Government is still limited, with most of the information shared being tacit and informal. In addition, the implementation of talent management tends to be unfair, with some employees feeling that they do not get equal opportunities in career development. Factors that influence talent retention include job satisfaction, career development opportunities, compensation, and organizational culture. This study also found that the integration of KM and talent management can strengthen talent retention strategies, but challenges related to technological infrastructure, inequality in career opportunities, and lack of an integrated system are still obstacles.